De Novo Missense Variants in SLC32A1 Cause a Developmental and Epileptic Encephalopathy Due to Impaired GABAergic Neurotransmission. Issue 6 (8th September 2022) - Platzer, Konrad; Sticht, Heinrich; Bupp, Caleb; Ganapathi, Mythily; Pereira, Elaine M.; Le Guyader, Gwenaël; Bilan, Frederic; Henderson, Lindsay B.; Lemke, Johannes R.; Taschenberger, Holger; Brose, Nils; Abou Jamra, Rami; et al.
Abstract : Objective: Rare inherited missense variants in SLC32A1, the gene that encodes the vesicular gamma‐aminobutyric acid (GABA) transporter, have recently been shown to cause genetic epilepsy with febrile seizures plus. We aimed to clarify if de novo missense variants in SLC32A1 can also cause epilepsy with impaired neurodevelopment. Methods: Using exome sequencing, we identified four individuals with a developmental and epileptic encephalopathy and de novo missense variants in SLC32A1 . To assess causality, we performed functional evaluation of the identified variants in a murine neuronal cell culture model. Results: The main phenotype comprises moderate‐to‐severe intellectual disability, infantile‐onset epilepsy within the first 18 months of life, and a choreiform, dystonic, or dyskinetic movement disorder. In silico modeling and functional analyses reveal that three of these variants, which are located in helices that line the putative GABA transport pathway, result in reduced quantal size, consistent with impaired filling of synaptic vesicles with GABA. The fourth variant, located in the vesicular gamma‐aminobutyric acid N‐terminus, does not affect quantal size, but increases presynaptic release probability, leading to more severe synaptic depression during high‐frequency stimulation. Thus, variants in vesicular gamma‐aminobutyric acid can impair GABAergic neurotransmission through at least two mechanisms, by affecting synaptic vesicle filling and by altering synaptic short‐term plasticity. Interpretation: This work establishes de novo missense variants in SLC32A1 as a novel cause of a developmental and epileptic encephalopathy. Summary for Social Media If Published: @platzer_k @lemke_johannes @RamiJamra @Nirgalito @GeneDx The SLC family 32 Member 1 (SLC32A1) is the only protein identified to date, that loads gamma‐aminobutyric acid (GABA) and glycine into synaptic vesicles, and is therefore also known as the vesicular GABA transporter (VGAT) or vesicular inhibitory amino acid transporter (VIAAT). Rare inherited missense variants in SLC32A1, the gene that encodes VGAT/vesicular inhibitory amino acid transporter, have recently been shown to cause genetic epilepsy with febrile seizures plus. We aimed to clarify if de novo missense variants in SLC32A1 can also cause epilepsy with impaired neurodevelopment. We report on four individuals with de novo missense variants in SLC32A1 and a developmental and epileptic encephalopathy with infantile onset epilepsy. We establish causality of the variants via in silico modeling and their functional evaluation in a murine neuronal cell culture model. SLC32A1 variants represent a novel genetic etiology in neurodevelopmental disorders with epilepsy and a new GABA‐related disease mechanism. ANN NEUROL 2022;92:958–973